Misconceptions of the Pancasila Student Profile Strengthening Project by Teachers at the Sekolah Penggerak - Utami, Asih; Yunaini, Norma; Trisnani, Novy; Farid, Mohammad Ghufroni; Evitasari, Atika Dwi; Agus Kichi Hermansyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The Pancasila Student Profile is a descriptive framework that formulates the characteristics, attitudes, and fundamental values that are expected to be embedded in every student in Indonesia. This profile is formed based on the appreciation and practice of Pancasila values as the moral and ideological foundation of the nation. The Pancasila student profile has six elements, including (1) faith, fear of God Almighty, and noble character, (2) independence, (3) mutual cooperation, (4) global diversity, (5) critical reasoning, and (6) creativity. Although the Pancasila student profile is integrated into all intracurricular, co-curricular, extracurricular and habituation activities at school, the assessment of the Pancasila student profile is more focused on co-curricular activities, namely the project to strengthen the Pancasila student profile. This study aims to describe common misconceptions related to the project of strengthening the Pancasila student profile by teachers. The research method uses descriptive quantitative research, namely using questionnaires and interviews. The results of the study show that there is a misconception of teachers' understanding of PSPSP. These misconceptions are found in S2, S9, S1, S6, S10 and S5. The findings of teachers' misconceptions related to PSPSP encourage several important implications. Intensive socialization and training for teachers is needed, structured learning guides and modules, monitoring and evaluation are needed to ensure the suitability of practices with the goals and values of the Pancasila student profile.